An Interview With Rita Dove. - Schwartz, Claire (Virginia Quarterly Review)
An interview with African American poet and author Rita Dove is presented. The topics of the interview include her poetry collections, including "On the Bus With Rosa Parks" and "Sonata Mulattica," the useful language systems that she has been working with and the use of the online social networking site Twitter to publish poems.